Effective Endoscopic Ultrasound-Guided Transgastric Drainage in a Case of Subcutaneous Intractable Postoperative Pancreatic Fistula - Yamamoto, Kazuyuki; Hurukawa, Shotaro; Tsuchikawa, Takahiro; Shichinohe, Toshiaki; Matsumoto, Joe; Nasu, Yuya; Hirano, Satoshi; Kato, Kentaro; Kondo, Satoshi; Tanaka, Eiichi (Nippon Shokaki Geka Gakkai zasshi, 2012)
We report a case with postoperative pancreatic fistula successfully treated by endoscopic transgastric drainage. A 79-year-old man with cancer of the head of the pancreas underwent subtotal stomach-preserving pancreatoduodenectomy. On postoperative day 9, based on a high amylase level in drainage fluid, we suspected postoperative pancreatic fistula. The drainage tube was withdrawn on the 26th postoperative day after confirming closure of the fistula. He complained of upper abdominal pain and fever on the 36th postoperative day. CT scan revealed an abdominal fluid collection 2.5 cm in diameter around the pancreatojejunostomy. As percutaneous drainage was abandoned due to the presence of the small bowel between the abdominal wall and the lesion, endoscopic ultrasound (EUS)-guided transgastric drainage was attempted. Immediately after the procedure, the patient recovered and became asymptomatic. Since EUS-guided transgastric drainage for postoperative pancreatic fistula appears to be safe and feasible, it is an option for selected patients.